TANGGUNG JAWAB INDONESIA TERHADAP PERLINDUNGAN HABITAT ORANGUTAN KALIMANTAN BERDASARKAN KONVENSI KEANEKARAGAMAN HAYATI 1992: Indonesia's Responsibility For The Protection Of The Kalimantan Orangutan Habitat Based On The 1992 Biodiversity Convention - Ariefandi Rahmat; Arlina Permanasari (Reformasi Hukum Trisakti, 2025)
The destruction of protected animal habitats due to the development of industries in the environmental sector has become an endless polemic from year to year. One of the most affected protected animals is the Bornean Orangutan, whose habitat has been destroyed due to land clearing for palm oil and other natural sector industries, bringing this primate to extinction. The problem formulated in this article is: how is Indonesia's responsibility in protecting the habitat of the Bornean Orangutan according to International Environmental Law and how is Indonesian government policy in protecting habitat of the Bornean Orangutan based on the Convention on Biological Diversity and Forestry Principles? This article is a normative legal research, descriptive in nature, qualitative data analysis, and using deductive logic. This article concludes that based on principle of state responsibility in International Environmental Law, Indonesia has responsibility for the unavoidable destruction of habitat, is obliged to make legal rules regarding animal protection, and makes efforts to preserve Bornean Orangutan and its habitat. Policies that can be carried out by Indonesian government must refer to Articles 8 and 9 of 1992 Convention on Biological Diversity through in-situ and ex-situ conservation and maintenance of forest functions based on Forestry Principles.